Partisipasi Masyarakat Dalam Pengelolaan Sampah (Studi pada Tempat Pengolahan Sampah Terpadu (TPST) Sumedang Bersatu Desa Cepokomulyo Kecamatan Kepanjen Kabupaten Malang) - Santos Rimba Bhirawan (Jurnal Administrasi Publik, 2016)
Abstract: People Participation to Garbage Management (Study in Sumedang Bersatu Integrated Garbage Treatment Facilities at Cepokomulyo Village Sub district of Kepanjen in the Regency of Malang). Basically, development process and environment have a mutual relationship which can give influence each other. Development is based on environment and environment does, either. Garbage management became one of major community problems to be solved by Government, recently. Community participation in keeping a good sanitation, especially by solving some garbage management problems, was expected by Government. Basically, garbage management contain of some processing stages such as container packaging, accumulation, transportation, and manufacturing of garbage. Result showed that people participation of garbage management in Cepokomulyo Village was good enough because people has participated directly and indirectly, either. However, there still be a lack information in garbage sorting and manufacturing process. Government must be more active to give information to the people about community-based garbage management so that they will be more understand about the functions and benefits of garbage. Keywords: people’s participation, garbage management Abstrak: Partisipasi Masyarakat dalam Pengelolaan Sampah (Studi pada Tempat Pengolahan Sampah Terpadu (TPST) Sumedang Bersatu Desa Cepokomulyo Kecamatan Kepanjen Kabupaten Malang). Pada dewasa ini pola pemerintah telah mempunyai konsep pembangunan yang arahnya untuk meningkatkan pean serta masyarakat dalam pembangunan. Salah satu bentuk permasalahan yang dihadapi pemerintah sekarang ini adalah tentang sampah. Keterlibatan masyarakat dalam menjaga kebersihan lingkungan dengan ikut aktif mengelola masalah persampahan sangat diharapkan oleh pemerintah. Pada dasarnya pengelolaan sampah terdiri atas beberapa tahapan proses antaralain, pewadahan, pengumpulan, pengangkutan, pengolahan. Partisipasi masyarakat Desa Cepokomulyo dalam pengelolaan sampah sudah cukup baik karena masyarakat ikut berpartisipasi secara langsung maupun tidak langsung. Tetapi masih ada kekurangan dalam hal pemilahan sampah dan pengolahan sampah. Pemerintah diharapkan bisa terus memperhatikan masyarakat agar program pengelolaan sampah bisa berjalan dengan baik dan menghasilkan keuntungan. Kata kunci: partisipasi masyarakat, pengelolaan sampah